2008
DOI: 10.1080/10934520701781178
|View full text |Cite
|
Sign up to set email alerts
|

Early neurotoxic effects of inhalation exposure to aluminum and/or manganese assessed by serum levels of phospholipid-binding Clara cells protein

Abstract: Little is known on the disturbances of lung epithelium function in aluminum casting smelters and shipyard welders exposed by inhalation to irritant occupational pollutants, dust and fumes. The exact mechanism of aluminum and manganese toxicity is not known, but it is thought that they may potentiate oxidative and inflammatory stress, leading to impaired neurological function. The aim of the study was to investigate the subclinical effects of aluminum and manganese exposure on the nervous system and to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…[32] A similar picture is observed in welders occupationally exposed by inhalation to gases and dusts from welding fumes containing Mn or in aluminum smelter workers exposed to dusts containing aluminum, and in copper smelter workers exposed to arsenic. [33,34] Exposure to arsenic causes significant changes in the kidneys. In this study we observed increased urinary levels of low molecular weight protein β 2 M and RBP, and the increase was statistically significant in Furnace Department workers ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[32] A similar picture is observed in welders occupationally exposed by inhalation to gases and dusts from welding fumes containing Mn or in aluminum smelter workers exposed to dusts containing aluminum, and in copper smelter workers exposed to arsenic. [33,34] Exposure to arsenic causes significant changes in the kidneys. In this study we observed increased urinary levels of low molecular weight protein β 2 M and RBP, and the increase was statistically significant in Furnace Department workers ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence signal of metal ion treated cells, particularly in the context of Ti(III), sufficiently increased to a level where we could be sure that any background fluorescence from native metal ion complexes was essentially insignificant. In addition, a significant increase of the fluorescent signal was seen for Al, Cr(III), Mo, Ni and Ti(IV), all metals that have been reported to be either neurotoxic or nominated to play a role in chronic nervous diseases (Campbell et al, 2004;Halatek et al, 2008;Smorgon et al, 2004;Song et al, 2008;Wang et al, 2008;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Sudden, acute intoxication with high metal concentrations causes usually significantly correlated, unequivocal neurotoxic symptoms, as described for Cr, cobalt (Co) and lead (Pb) (Gobba, 2003;Halatek et al, 2008;Kumar, 2001;Pecze et al, 2005;Song et al, 2008). Little is known about long-term exposure to lower 0165-0270/$ -see front matter © 2008 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…Although such a pattern is not always seen [8], it remains controversial as to whether aluminium is necessarily a causative agent in the development of Alzheimer's disease [9]. However, there continue to be reports in which impaired cognitive function is associated with industrial exposure to aluminium [10][11][12][13]. Although a link between aluminium and Alzheimer's disease is debatable, there is clear evidence that aluminium can cause severe encephalopathy in patients being dialysed for kidney disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium can be measured in a person's plasma (or serum) [16] and urine [13], but this will reflect short term exposure, which is certainly valuable, but not well suited to assessing whether cumulative exposure could be causally related to specific health effects. The presence of aluminium can be clearly demonstrated by taking a biopsy and using the appropriate staining technique [17,18].…”
Section: Introductionmentioning
confidence: 99%